RELEVANSI HADIS TENTANG WALI NIKAH DI ZAMAN MODERN (IAIN Tulungagung, 2022)
The position of the marriage guardian is based on the perspective of placing the guardian as a representative who can protect the prospective bride from psychological aspects related to her emotions and psychology, related to public views, to the prospective bride which can cause sociological losses. The guardian of marriage in the context of hadith is an obligation, this is relevant to the development of modern times today. From a legal perspective, marriage in Indonesia has reduced the need for a guardian. So, in the context of the relevance of the hadith regarding marriage guardians in modern times, it is a form of necessity as a form of legal protection for dignity (hifzul 'irdh). So important is the marriage guardian in a marriage as a form of sincerity and has a sacred value, the prospective bride and groom must ask permission from their guardian as a form of blessing to undergo a marriage.